2018
DOI: 10.1016/j.celrep.2018.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Quantification of the Modified Proteome Reveals Oxidative Heart Damage in Mitochondrial Heteroplasmy

Abstract: Post-translational modifications hugely increase the functional diversity of proteomes. Recent algorithms based on ultratolerant database searching are forging a path to unbiased analysis of peptide modifications by shotgun mass spectrometry. However, these approaches identify only one-half of the modified forms potentially detectable and do not map the modified residue. Moreover, tools for the quantitative analysis of peptide modifications are currently lacking. Here, we present a suite of algorithms that all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Mitochondrial pathways are involved in many diseases, including malignant tumors, diabetes, Parkinson’s disease, Alzheimer’s disease, and cardiovascular disease [ 10 , 11 ]. Thus, mitochondrial proteomics has become a hotspot in the study of disease to discover new biomarkers and molecular targets for drug discovery and therapeutic intervention in recent years [ 12 ]. Our previous studies identified 5115 mitochondrial expressed proteins (mtEPs) and 70 statistically significant KEGG pathways based on 5115 mtEPs in human OCs [ 13 ], which provided the mitochondrial protein expression profiling and overall pathway profiling in human OC.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial pathways are involved in many diseases, including malignant tumors, diabetes, Parkinson’s disease, Alzheimer’s disease, and cardiovascular disease [ 10 , 11 ]. Thus, mitochondrial proteomics has become a hotspot in the study of disease to discover new biomarkers and molecular targets for drug discovery and therapeutic intervention in recent years [ 12 ]. Our previous studies identified 5115 mitochondrial expressed proteins (mtEPs) and 70 statistically significant KEGG pathways based on 5115 mtEPs in human OCs [ 13 ], which provided the mitochondrial protein expression profiling and overall pathway profiling in human OC.…”
Section: Introductionmentioning
confidence: 99%
“…But also proteomic approaches suffer from the plethora of possible end products; allowing too many variable modifications leads to a combinatorial explosion of the search space and a concomitant loss of statistical power [122]. Novel search strategies have therefore been developed either based on dependent peptides [123] or wide precursor mass tolerance [124]. While these search strategies are better suited to deal with a large number of defined PTMs, they do not ameliorate the fundamental problem of undefined modifications such as random crosslinks between molecules.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Alternatively, it has also been shown that the presence of heteroplasmy, in genotypes which are healthy when present at 100%, can induce fitness disadvantages (Acton et al 2007;Sharpley et al 2012;Bagwan et al 2018). In cases where heteroplasmy itself is disadvantageous, especially in later life where such mutations may have already accumulated, accelerating heteroplasmy variance increase to achieve fixation of a species could be advantageous.…”
Section: Control Strategies Against Mutant Expansionsmentioning
confidence: 99%